2022
DOI: 10.1186/s12864-022-08396-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic characterization of the molecular mechanisms induced by RGMa during skeletal muscle nuclei accretion and hypertrophy

Abstract: Background The repulsive guidance molecule a (RGMa) is a GPI-anchor axon guidance molecule first found to play important roles during neuronal development. RGMa expression patterns and signaling pathways via Neogenin and/or as BMP coreceptors indicated that this axon guidance molecule could also be working in other processes and diseases, including during myogenesis. Previous works from our research group have consistently shown that RGMa is expressed in skeletal muscle cells and that its overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…MuSCs in cluster 6 expressed high levels of genes encoding ribosomal proteins ( Rps2 and Rpl3 ) and genes expressed during the pre-fusion phase ( Myof ). 50 Furthermore, a subset of MuSCs in clusters 8 and 9 displayed high levels of myogenic genes ( Myog , Fig. 1D ; Itga7 , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MuSCs in cluster 6 expressed high levels of genes encoding ribosomal proteins ( Rps2 and Rpl3 ) and genes expressed during the pre-fusion phase ( Myof ). 50 Furthermore, a subset of MuSCs in clusters 8 and 9 displayed high levels of myogenic genes ( Myog , Fig. 1D ; Itga7 , Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, it is common that adults affected by Type 2 Diabetes, lose skeletal muscle mass 29 . It has also been shown that certain Pou2f1 isoforms were either heavily up-or downregulated by Repulsive guidance molecule a (RGMa), important in skeletal cell differentiation, cell fusion and hypertrophy 30 , which could contribute to explain the gradient between heavy-type and light-type horses. In livestock, MAGI1 was previously associated with average daily gain and Kleiber ratio (average daily gain / end weight 0.75 ) in 6-to 9month-old sheep 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In the Brazilian Nellore cattle, a QTL containing the POU2F1 gene explained 41% of genetic variance in conformation and 29% in muscling scores 33 and was also identified as one of the major transcription factors regulating growth and fatty deposits in Iberian × Landrace pigs 34 . In humans, certain Pou2f1 isoforms were either heavily up- or downregulated by repulsive guidance molecule a (RGMa), important in skeletal cell differentiation, cell fusion and hypertrophy 35 . POU2F1 variants were also associated with human Type 2 Diabetes Mellitus 36 , 37 , and it is common that adults affected by Type 2 Diabetes lose skeletal muscle mass 38 .…”
Section: Discussionmentioning
confidence: 99%